Effects of Grain Size, Reducing Sugar Content, Temperature and Pressure on Caking of Raw Sugar - Pakamon Chitprasert,; Jirawate Chedchant,; Penkhae Wanchaitanawong,; Ngamtip Poovarodom, (Agriculture and Natural Resources, 2006)
This work aimed to study the factors contributing to cake formation of raw sugar. They were grain size, reducing sugar content, temperature, and pressure during storage. From the water vapour adsorption isotherms, the grain size was found to have the largest influence on the hygroscopic properties of raw sugar. At 30°C, the largest (>1.000 mm) and smallest (<0.425 mm) raw sugar grain had the highest and lowest critical relative humidity (CRH) or caking point at 79.5% and 73.2%, respectively. Scanning electron micrograph (SEM) revealed that raw sugar, exposed to the 67.89% RH and 30°C, established a contact between crystals and fine particles. The fine particles also play a role as binder. With the consolidation pressure of 1.5 kg/cm2 on a sugar pile, the temperature within the pile did not significantly increase enough to stimulate the cake formation. These results indicate that key factors in preventing the caking of raw sugar is the control of grain size to be greater than 0.425 mm and RH to be less than 67.89% at 30°C during storage.